Informal meeting on steel box girder bridges April 1972 - Hardy, B. J. (Institution of Civil Engineers, 1973)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of an informal joint meeting with Institution of Highway Engineers and IStructE held on 25 April 1972.